Implementing Dynamic Capability Framework on Indonesian Schools - Sabilil Muttaqin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The article was an investigation into the nature of organisational sustainability in Indonesian schools. Through an extensive reading and analysis of literature on organisational studies, this research examined the possibility of integrating key aspects of learning from change situations into systemic approaches to the organisational design of schools in Indonesia. Within Indonesia’s educational context, continually changing environmental conditions were made even more problematic for schools because political and public policy instability regularly enters their organisational life and educational projects. The reasons were multifarious and nuanced as to how they impact schools working in particular contexts, including: (1). Regular and significant curriculum change policies in recent years; (2) Public policy change and expectations for addressing change at the school level within very short time frames; and (3) How an ever-changing policy environment was made more complex for those schools located in geographically isolated locales within large scale logistical considerations for the Indonesian schools that must adapt, adopt or fail. The result show that key dimensions of Dynamic Capability was pertinent as an approach to investigate and understand the adaptation process of Indonesian schools. The three core components of dynamic capability namely, sensing, seizing, and transforming were recommended as a way to portray schools’ actions toward the uncertain public policy in Indonesia. Keywords: Dynamic Capability, Organisational Sustainability, Adaptive School Design